A study of language use in daily interactions among Romblomanon speakers - Manalon, Josefa Belleza 1929- (1976)
The purpose of this paper was to find out the language choice of the people in different situations about certain topics, and with various types of interlocutors. It sought to answer which of the four vernacular languages, English, Filipino, Spanish, and the vernacular is used on what occasions, talking about what topics of conversation, and with whom. It also pointed out how borrowing or mixing has become a part of the everyday speech and the functions it serves. The study employed the normative-survey and descriptive methods with the questionnaire as the main instrument in gathering data.
"June, 1976."
Vita.
Thesis (Master of Arts (English as a Second Language))--University of the Philippines, Diliman.
Keywords: Education, Bilingual -- Philippines -- San Agustin (Romblon); Native language and education -- Philippines -- San Agustin (Romblon); English language -- Study and teaching -- Romblomanon speakers